Spin-dependent transport in vacancy-defected carbon nanotubes with metal atom doping - G.R. Berdiyorov (7170563) (2025)
Spin-polarized quantum transport calculations are conducted for metallic carbon nanotubes (CNTs) containing a single vacancy defect terminated either by unsaturated carbon atoms or by pyridinic nitrogen atoms. The conductivity of the system with pyridinic nitrogen is consistently higher than that of CNTs with reconstructed vacancy defects. The influence of metal atoms on the transport properties of CNTs strongly varies depending on the nature of the vacancy defect: while metal atoms increase conductivity in carbon-terminated defects, they lead to reduced conductivity in pyridinic defects. The pyridinic system also exhibits an enhanced spin dependency in charge transport, which could be advantageous for exploiting spintronic nanodevices. Other Information Published in: Solid State Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ssc.2025.116007